The Influence Of The Village Musyawarah Aspiration Network, Strategic Planning, And The Role Of Community Leaders On The Opportunities For The Growth Of Small Micro Scale Enterprise In Fakfak District - Jais Zulkarnain Iha; Nanik Kustiningsih; Choirul Anam; Rifda Fitranti (Jurnal Scientia, 2024)
The Village Consultative Body is an organization that functions as a body that establishes village regulations together with the Village Head, accommodates and channels community aspirations. The research aims to determine the influence of village consultation aspiration networks, strategic planning, and the role of community leaders on opportunities for the growth of micro and small scale businesses in Fakfak Regency. Descriptive research method with a quantitative analysis approach. Data was obtained through a direct survey of respondents who had been determined deliberately. The data obtained is given a weight value based on assessment indicators obtained from the results of preliminary research. Test the validity and reliability of the data in a gradual and structured manner using a triangulation and role sharing approach. The research results are presented in the form of a spider web diagram which is equipped with illustrations of shift share gap values, Pearson correlation analysis , and regression equation models obtained from the SPSS version 2.3 statistical tool.